Conceptualizing humanity in the English School. Issue 2 (13th April 2016) - Gallagher, Adrian
Abstract : The article advances three options to create new ways for thinking about humanity. First, reject humanity and view interconnectedness as state centric rather than human centric, with international law upheld as the bedrock institution of international society. Second, thin humanity puts forward a reductionist view that the value of humankind lies in the human worth of its members – human beings. In short, humanity is the sum of its parts. Third, thick humanity, which views humankind as an independent value in its own right. From this perspective, the value of humanity lies in its ubiquity, which reveals that it is not just more, it is different, to the sum of its parts. It is important to note that this is not a purely theoretical issue. One's view of humanity shapes one's view of whether citizens of one state should care for the citizens of another, which lies at the heart of contemporary debates over issues such as the responsibility to protect, human security, and redistributive justice. In so doing, the article speaks to broader debates on humanity that reflects the need for greater interdisciplinary research in the future.